THE IMPLEMENTATION OF INFORMATION GAP ACTIVITIES TO IMPROVE STUDENTS’ SPEAKING AND READING SKILLS - Nurdevi Bte Abdul (Universitas Muhammadiyah Makassar, 2013)
This study was conducted to know whether or not the use of Information Gap Activities improves students’ accuracy in speaking skill that covers three elements of accuracy; vocabulary, pronunciation, and grammar; and to know whether or not the use of Information Gap Activities improves students’ literal comprehension in reading skill. This research applied a quasi-experimental design; the nonequivalent control group design. It used two groups; experimental groups and control group. The data obtained from the test was analyzed quantitatively and then its’ result was compared with t-table to know whether they were significantly different or not. The data showed students’ mean score of accuracy in speaking skill and literal comprehension in reading skill improved after teaching by using Information Gap Activities. In experimental class, the students’ accuracy of pretest was 1.55 and improved to be 3.06 in posttest, students’ literal comprehension of protest was 0.82 and posttest was 3.21. In control class, the students’ accuracy was 1.90 for pretest and 2.32 for posttest; students’ literal comprehension was 1.63 for pretest 2.27. These findings indicate that the mean score of pre-test was greater than pretest for that both class. However, the students’ mean score in experimental was greater than control class where accuracy (3.062.37) and literal comprehension (3.212.27). It meant that implementing Information Gap activities were effective to improve the students’ speaking and reading skills.Keywords: Speaking and reading skills, accuracy, literal comprehension, Information Gap Activities